Step-by-step explanation:
your don't see what went wrong ?
Tyrell worked on
16 - 2(4 + 3x)
what do brackets mean ? they mean that this operation has to be done before everything else in the expression.
as this contains a variable, we cannot fully calculate it, true, but we need to keep this in mind and always treat the content of the brackets as one package.
so, whatever I do from the outside with one part of that package, I have to do also with all the other parts of that package.
so, the multiplication with -2 has to happen with both : 4 and 3x. not just with 4.
therefore, the correct simplification looks like
16 - 8 - 6x
8 - 6x or -6x + 8
Amelia multiplied correctly, but then made a mistake summing things up
10x - 3(4x + 1)
10x - 12x - 3
10x - 12x = -2x
I can't mix the pure constant -3 into the factors of x. that would be like the famous mixing of apples and oranges.
so, the result is
-2x - 3
Answer:
The first 5 terms are -6,-25,-44,-63 and -82
The sequence is arithmetic
Step-by-step explanation:
Given that A(n + 1) = A(n) − 19 for n ≥ 1 and A(1) = −6
A(1) = -6
A(2) = A(1) − 19 = -6 - 19 = -25
A(3) = A(2) − 19 = -25 - 19 = -44
A(4) = A(3) − 19 = -44 - 19 = -63
A(5) = A(4) − 19 = -63 - 19 = -82
So the first 5 terms are -6,-25,-44,-63 and -82
If they are in arithmetic the common difference will be same, if geometric common ratio will be same.
Let us check common difference,
-25-(-6) = -19
-44-(-25) = -19
-63-(-44) = -19
-82-(-63) = -19
So common difference is same, so the sequence is arithmetic.
Answer:
.69
Step-by-step explanation:
Answer:
30%
Step-by-step explanation:
you just add 10% and 20%
Hope it helps c: